1980
DOI: 10.1055/s-2007-999171
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol Binding Reserve and High Density Lipoprotein Cholesterol in Patients on Maintenance Hemodialysis

Abstract: Serum cholesterol binding reserve (SCBR, the capacity of the serum to solubilize additional cholesterol), high density lipoprotein cholesterol (HDL . Ch) and serum levels of cholesterol and triglycerides were measured in 53 chronically uremic patients (40 men and 13 women) undergoing maintenance hemodialysis. The values were compared with those of controls (149 men and 28 women) matched for serum lipid levels. Hypertriglyceridemia and decreased HDL . Ch were observed among the patients, confirming previous rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The present study confirms previously well-known lipid anomalies in ufaemic patients treated or untreated by intermittent haemodialysis, i. e., hypertriglyceridaemia, a decrease of serum HDL-cholesterol and an increase of the so-called cardiovascular risk factors (13,15,16,(18)(19)(20)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In addition, we have demonstrated that lipid anomalies were more marked in uraemic patients with more advanced renal failure than in those with moderate renal insufficiency.…”
Section: Discussionsupporting
confidence: 90%
“…The present study confirms previously well-known lipid anomalies in ufaemic patients treated or untreated by intermittent haemodialysis, i. e., hypertriglyceridaemia, a decrease of serum HDL-cholesterol and an increase of the so-called cardiovascular risk factors (13,15,16,(18)(19)(20)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In addition, we have demonstrated that lipid anomalies were more marked in uraemic patients with more advanced renal failure than in those with moderate renal insufficiency.…”
Section: Discussionsupporting
confidence: 90%
“…These data indicate that during statin treatment it is mainly the cholesterol-dependent lipoprotein binding capacity in the circulation that will determine the 4β-OH-cholesterol concentration in plasma, rather than a direct effect on the hepatic CYP3A4 enzyme. A disturbed cholesterol-dependent lipoprotein binding capacity in HD patients may also be operative [ 46 ]. Taken together, our results suggest that the ratio 4β-OH-cholesterol/cholesterol rather than 4β-OH-cholesterol alone, is the preferred measure of CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The lower the SCBR the higher the tendency to develop atherosclerosis and hence the higher the risk of coronary heart disease. 6 Reverse cholesterol transport prevent deposition of cholesterol in tissue and thought to be antiartherogenic and HDL cholesterol level has been shown to low risk of coronary heart disease. 3 Acute myocardial infarction (AMI) and unstable angina are now recognized as part of a spectrum of clinical disease collectively known as acute coronary syndromes (ACS).…”
Section: Introductionmentioning
confidence: 99%